THE ROLE OF ISLAMIC EDUCATION IN ENHANCING TOLERANCE AND HARMONY AMONG RELIGIOUS COMMUNITIES - Syaiful Bahri Djamarah (CV. ADIBA AISHA AMIRA, 2025)
This study aims to examine the role of Islamic education in improving tolerance and harmony among religious communities through a literature review. Islamic education not only instils values of faith but also teaches the importance of mutual respect and peaceful coexistence amid diversity. This study examines the concept of Islamic education related to tolerance and harmony, as well as the implementation of Islamic education in fostering these attitudes through curriculum, teaching methods, and religious social activities. The results of this study indicate that Islamic education can be an eflective medium in shaping an inclusive generation that is able to accept diflerences and actively maintain harmony in society. Thus, Islamic education has a strategic contribution in maintaining peace and harmony among religious communities in a pluralistic society.